THE EXISTENCE OF ALBASIA PLANTS IN CIKARAMAS VILLAGE: A CASE STUDY OF ALBASIA CULTIVATION IN CIKARAMAS VILLAGE, SUMEDANG REGENCY, WEST JAVA - Hamda Khairuzani (Universitas Pakuan, 2022)
With forestry development, it is hoped that national development goals will be achieved, in particular the improvement of living standards and community welfare accompanied by improvement of their living environment. Wood is one of the main forest products, which is needed by the community to meet various needs of human life. Although nowadays there are many synthetic materials that can substitute the use of wood, the demand for wood for various purposes is still quite high and even shows an increasing demand. The benefits of this wood are growing, starting from the need for wood for energy, building materials, wood pulp, furniture, to the use of wood for aircraft fuselages. The planting of sengon trees by the community in Cikaramas Village is quite developed and is very suitable considering the topography and land conditions that are suitable for the place where sengon trees grow. Then it becomes a separate added value, if farmers/communities are able to optimize inputs for forest plant cultivation by knowing in advance the characteristics/characteristics of the soil. Albasia that developed in Cikaramas Village, is part of the knowledge system of Cikaramas Village residents about timber plants. The system is a legacy of knowledge about the types and uses of woody plants for subsistence needs used for building materials. Prior to the development of albasia, wood plants of the type of tissue, jackfruit wood, and the type of